2010
DOI: 10.4049/jimmunol.1002156
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin as an Adjuvant: Cellular Mechanisms and Potential

Abstract: Flagellin is a potent activator of a broad range of cell types involved in innate and adaptive immunity. An increasing number of studies have demonstrated the effectiveness of flagellin as an adjuvant, as well as its ability to promote cytokine production by a range of innate cell types, trigger a generalized recruitment of T and B lymphocytes to secondary lymphoid sites, and activate TLR5+CD11c+ cells and T lymphocytes in a manner that is distinct from cognate Ag recognition. The plasticity of flagellin has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
307
3
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(321 citation statements)
references
References 76 publications
6
307
3
5
Order By: Relevance
“…Flagellin-triggered responses exert various effects on different cells, tissues and organs; these responses vary greatly according to the dose, physiological condition of the cell, the animal used and the experimental setting. 15,17,26 However, the beneficial flagellinactivated responses for host defenses and the potential adverse effects of flagellin in different organs can be contradictory. Therefore, the flagellin-triggered pathophysiological responses should be explored further to provide a clearer understanding of the correlation between the pattern recognition receptors (PRRs)-flagellin interaction and its pathophysiological effects to enhance the application of recombinant flagellin as a prophylactic and therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flagellin-triggered responses exert various effects on different cells, tissues and organs; these responses vary greatly according to the dose, physiological condition of the cell, the animal used and the experimental setting. 15,17,26 However, the beneficial flagellinactivated responses for host defenses and the potential adverse effects of flagellin in different organs can be contradictory. Therefore, the flagellin-triggered pathophysiological responses should be explored further to provide a clearer understanding of the correlation between the pattern recognition receptors (PRRs)-flagellin interaction and its pathophysiological effects to enhance the application of recombinant flagellin as a prophylactic and therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an increasing number of studies have used flagellin as an adjuvant because of its ability both to promote cytokine production by a range of innate cell types and to trigger adaptive immune responses in a manner that is distinct from cognate antigen recognition. 15 Furthermore, flagellin has the potential to be used as a biological protectant against both major acute radiation syndrome during cancer radiotherapy and a mitigator of radiation emergencies. 6 Vijay-Kumar et al 16 demonstrated that the systemic administration of flagellin might be a relatively safe means of providing temporary nonspecific protection against chemical, bacterial, viral and radiation challenge.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an increasing number of studies have demonstrated the effectiveness of membrane-anchored flagellin as a mucosal adjuvant, as well as its ability to promote cytokine expression by innate immune cells and trigger the generalized recruitment of T-and B-lymphocytes to secondary lymphoid organs (Mizel & Bates, 2010). For instance, overexpression of flagella has been shown to enhance the induction of an antigen-specific immune response in macrophages and vaccination with a live attenuated strain of S. Typhimurium that produces two flagellin proteins (FliC and FljB) induced protective immune responses against oral challenge with virulent S. Typhimurium (Eom et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The endotoxin value of the purified recombinant flagellin preparation was ,0.03 EU/mg. Any contamination with other PAMPs was assessed using the purified proteins to stimulate the flagellinnonresponsive RAW264.7 cells 25,26 overnight at the concentration of 4000 nM.…”
Section: Animalsmentioning
confidence: 99%